PubMed 문헌 분석을 통한 한약재 네트워크 다차원 분석 시스템 개발 - 서동민(Dongmin Seo); 유석종(Seok Jong Yu); 이민호(Min-Ho Lee); 예상준(Sang-Jun Yea); 김철(Chul Kim) (한국콘텐츠학회 논문지, 16(6), 2016)
With the development of genomics, wearable device and IT/NT, a vast amount of bio-medical data are generated recently. Also, healthcare industries based on big-data are booming and big-data technology based on bio-medical data is rising rapidly as a core technology for improving the national health and aged society. Also, oriental medicine research is focused with modern research technology and validate it's various biochemical effect by combining with molecular biology technology. However there are few searching system for finding biochemical mechanism which is related to major compounds in oriental medicine. Therefore, in this paper, we collected papers related with medical herbs from PubMed and constructed a medical herbs database to store and manage chemical, gene/protein and biological interaction information extracted by a literature analysis on the papers. Also, to supporting a multidimensional analysis on the database, we developed a network analysis system based on a hierarchy structure of chemical, gene/protein and biological interaction information. Finally, we expect this system will be used the major tool to discover various biochemical effect by combining with molecular biology technology. 최근 유전체학의 발전, 웨어러블 디바이스의 확산, IT/NT의 발전 등에 따라 방대한 양의 바이오-메디컬 데이터가 생산되고, 이에 따라 빅데이터를 활용한 헬스케어 산업이 급속히 발달하고 있으며, 이와 관련된 빅데이터 기술은 국민의 건강 증대와 건강한 고령 삶을 제공하는 핵심 기술로 급부상하고 있다. 또한, 한의학에 대한 과학적 접근이 진행되면서 한약재 성분의 효능을 검증하고자 하는 다양한 분자 생물학 분야의 연구가 진행되고 있다. 하지만 관련 한약재의 주요 성분과 관련된 생화학적 기작을 손쉽게 검색할 수 있는 시스템이 갖추어져 있지 못한 실정이다. 그래서 본 논문에서는 PubMed로부터 한약재와 관련된 논문들을 수집후, 수집된 논문들에 대한 문헌 분석을 통해 추출된 한약재 관련 화합물, 유전자 그리고 생물학적 상호작용 정보를 저장 및 관리하는 한약재 정보 데이터베이스를 구축했다. 또한, 연구자들에게 구축한 한약재 정보 데이터베이스에 대한 직관적 분석을 제공하기 위해 화합물, 유전자 그리고 생물학적 상호작용 정보간 계층구조를 기반으로 네트워크를 구성 후, 해당 네트워크에 대한 다차원 분석을 제공하는 시스템을 개발했다. 마지막으로, 본 시스템은 향후 다양한 한약재 성분의 효능 및 생물학적 기작을 파악하는데 중요한 도구로 활용될 것으로 기대한다.